1999
DOI: 10.1002/etc.5620180722
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulation by heavy metals tested individually or in mixtures in rainbow trout (Oncorhynchus mykiss) exposed in vivo

Abstract: Abstract-The objective of this study was to evaluate the effect of heavy metals, at environmentally relevant concentrations, on the immune response of rainbow trout. Trout were exposed for 30 d to cadmium chloride (CdCl 2 ), mercuric chloride (HgCl 2 ), or zinc chloride (ZnCl 2 ) either individually or in combinations: CdCl 2 /HgCl 2 , CdCl 2 /ZnCl 2 , HgCl 2 /ZnCl 2 , or CdCl 2 /HgCl 2 /ZnCl 2 . Following the 30-d exposure, parameters of the nonspecific cellular immune response (phagocytosis, respiratory burs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(12 citation statements)
references
References 34 publications
(39 reference statements)
0
12
0
Order By: Relevance
“…In particular, the MHC class I UBA gene was strongly downregulated in liver under both acute and chronic exposures (Table VI). Mercury exposure has been shown to lead to immune suppression in fish (Sanchez‐Dardon et al , 1999) and is also associated with development of autoimmune disease (Havarinasab et al , 2007). These immune system effects may be related to the previously discussed apoptosis effects because immune‐related cells undergo apoptosis with methylmercury exposure (Shenker et al , 1998).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the MHC class I UBA gene was strongly downregulated in liver under both acute and chronic exposures (Table VI). Mercury exposure has been shown to lead to immune suppression in fish (Sanchez‐Dardon et al , 1999) and is also associated with development of autoimmune disease (Havarinasab et al , 2007). These immune system effects may be related to the previously discussed apoptosis effects because immune‐related cells undergo apoptosis with methylmercury exposure (Shenker et al , 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The exposure of fish to sublethal doses of Cd and Cu altered the macrophage functions such as phagocytic activity and production of free radicals (Elsasser et al, 1986;Zelikoff, 1993), respiratory burst (Sanchez-Dardon et al, 1999) and the blastogenic and antibody-production responses of lymphocytes (Anderson et al, 1989;O'Neill, 1981;Thuvander, 1989). The effects of metal also affect the levels of circulating leukocytes, thus altering the blood cell ratios (Dick and Dixon, 1985;Murad and Houston, 1988;Nussey et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Sanchez-Dardon et al (1999) reported that heavy metal pollution affects lysozyme levels and causes alterations of immunoregulatory functions in fish. Our study revealed that chronic exposure to 0.5 or 5 mg l -1 of Cr (VI) suppressed serum lysozyme activity.…”
Section: Discussionmentioning
confidence: 99%